Feed intake, nutrient digestibility and nutrient retention in Atlantic salmon (Salmo salar L.) fed diets with different physical pellet quality - Aas, Turid Synnøve; Sixten, Hanne Jorun; Hillestad, Marie; Ytrestøyl, Trine; Sveier, Harald; Åsgård, Torbjørn (Journal of Fisheries, 2020)
Three feeds with different physical pellet quality but the same formulation were fed to Atlantic salmon for 97 days. Pellet quality was measured as bulk density, durability, fat leakage, hardness, water stability and porosity. The largest difference among the feeds was measured in hardness (201, 236 and 86 Newton for Diet 1, Diet 2 and Diet 3 respectively). The relative feed intake was highest in salmon fed Diet 2 and Diet 3 with no effects of pellet hardness. Growth and feed efficiency ratio were similar among all fish. The apparent digestibility of energy, dry matter, nitrogen and lipid was similar for all feeds, whereas the apparent digestibility of phosphorus and zinc was the lowest in Diet 3. Retention of energy, lipid and nitrogen was also similar for all feeds. Salmon fed Diet 1 and Diet 3 retained more phosphorus than those fed Diet 2. An increased retention of the digested zinc was found in salmon fed Diet 3. This study concludes that physical pellet quality affects feed intake and improve utilisation of feed in salmon if optimised properly. Moreover, pellet hardness can be optimised in commercial scale without compromising feed intake as it has no influence on feed intake.